We going to calculate this limit just putting the value of the limit in place of x:

`lim(x->2) (x^3-8)/(x-2) = (8-8)/(2-2) =>` `lim(x->2) (x^3-8)/(x-2) = 0/0`

The limit didn't work so we will try factoring.

By factoring (`x^3-8` ) in `(x - 2)(x^2+4x+4)` we get:

`lim(x->2) (x - 2)(x^2+4x+4)/(x - 2) = lim(x->2) (x^2+4x+4)`

We will put the value of the limit in place of x:

`lim(x->2) (x^2+4x+4)= 16`

**Your answer is `lim(x->2) (x^3-8)/(x-2) = 16.` **

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now